Toward Reconciling Radiocarbon Production Rates With Carbon Cycle Changes of the Last 55,000 Years - Köhler, Peter; Adolphi, Florian; Butzin, Martin; Muscheler, Raimund; Adolphi, Florian; 1 Alfred‐Wegener‐Institut Helmholtz‐Zentrum für Polar‐und Meeresforschung (AWI) Bremerhaven Germany; Butzin, Martin; 1 Alfred‐Wegener‐Institut Helmholtz‐Zentrum für Polar‐und Meeresforschung (AWI) Bremerhaven Germany; Muscheler, Raimund; 2 Department of Geology Lund University Lund Sweden (Paleoceanography and Paleoclimatology, 2022)
Since it is currently not understood how changes in 14C production rate (Q), and in the carbon cycle, can be combined to explain the reconstructed atmospheric Δ14C record, we discuss possible reasons for this knowledge gap. Reviewing the literature, we exclude that changes in the content of atoms in the atmosphere, which produce cosmogenic 14C after being hit by galactic cosmic rays, might be responsible for parts of the observed differences. When combining Q with carbon cycle changes, one needs to understand the changes in the atmospheric 14C inventory, which are partially counterintuitive. For example, during the Last Glacial Maximum, Δ14C was ∼400‰ higher compared with preindustrial times, but the 14C inventory was 10% smaller. Some pronounced changes in atmospheric Δ14C do not correspond to any significant changes in the atmospheric 14C inventory, since CO2 was changing simultaneously. Using two conceptually different models (BICYCLE‐SE and LSG‐OGCM), we derive hypothetical Qs by forcing the models with identical atmospheric CO2 and Δ14C data. Results are compared with the most recent data‐based estimates of Q derived from cosmogenic isotopes. Millennial‐scale climate change connected to the bipolar seesaw is missing in the applied models, which might explain some, but probably not all, of the apparent model‐data disagreement in Q. Furthermore, Q based on either data from marine sediments or ice cores contains offsets, suggesting an interpretation deficit in the current data‐based approaches. Key Points: No important change found in the level of precursor material, which produces cosmogenic radiocarbon after being hit by galactic cosmic rays. Transient changes in the bipolar seesaw are needed in applied carbon cycle models to improve interpretation of the radiocarbon cycle. Sediment core‐ and ice core‐based radiocarbon production rates differ systematically, suggesting missing processes. Bundesministerium für Bildung und Forschung (BMBF) http://dx.doi.org/10.13039/501100002347 Swedish Research Concil ...